1996
DOI: 10.1598/rrq.31.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Traversing the topical landscape: Exploring students' self‐directed reading‐writing‐research processes

Abstract: S This 7‐month naturalistic study investigated students' reading and writing engagements as they conducted a research investigation related to World War II. Students were free to choose their research topics, to search for and to select from source materials, and to write up and present their findings in their own way. The participants were 11‐ and 12‐year‐old pupils in an open‐concept school in Aberdeen, Scotland. Data took the form of fieldnotes, photocopies of research booklets and source texts, structured,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 14 publications
(6 reference statements)
0
16
0
1
Order By: Relevance
“…The superiority of the complete program is in line with findings of Guthrie et al (2004), who showed that a program (CORI: concept-oriented reading instruction) which combines strategy instruction with motivational support outperformed both a strategy instruction group and a traditional instruction group. Qualitative findings of Many, Fyfe, Lewis, and Mitchell (1996) underline that teaching with the aim to encourage reading for personal meaning can provide the motivational background for further use of reading strategies. The finding that achievement in reading comprehension was improved is satisfying.…”
Section: Discussionmentioning
confidence: 97%
“…The superiority of the complete program is in line with findings of Guthrie et al (2004), who showed that a program (CORI: concept-oriented reading instruction) which combines strategy instruction with motivational support outperformed both a strategy instruction group and a traditional instruction group. Qualitative findings of Many, Fyfe, Lewis, and Mitchell (1996) underline that teaching with the aim to encourage reading for personal meaning can provide the motivational background for further use of reading strategies. The finding that achievement in reading comprehension was improved is satisfying.…”
Section: Discussionmentioning
confidence: 97%
“…New developments in 21st century education such as online learning opportunities, pedagogical shifts and availability of Internet on mobile devices have put additional expectations on learners to take more initiative in their own learning. Many, Fyfe, Lewis, & Mitchell [6] argues that teachers need to model learning strategies such as predicting, questioning, clarifying, and summarizing, so that students will develop the ability to use these strategies on their own. Teachers also need to allow individual learners to approach a task in different ways using different strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, teaching SRL requires a keen awareness of students' needs and knowledge and effective use of sophisticated teaching strategies. However, when teachers are highly effective in this regard, they scaffold students' learning processes and foster forms of disciplined inquiry that may not be reached without such expert guidance (Brown & Campione, 1994;Many et al, 1996;Perry, 1998).…”
Section: Helping Teachers To Develop Practices That Promote Srlmentioning
confidence: 99%
“…Previous classroom-based research using mixed methods indicates children develop academically effective forms of SRL when they are engaged in complex meaningful tasks and have opportunities to: (a) choose learning processes and products, and criteria by which these are judged; (b) control the degree of challenge presented by tasks; (c) evaluate their own learning; and (d) work collaboratively with and seek feedback from peers and (Many, Fyfe, Lewis, & Mitchell, 1996;Perry, 1998;Turner, 1995). Furthermore, this research indicates that teachers' support for SRL includes scaffolding and other instructional techniques that ensure students acquire the domain and strategy knowledge they need to operate independently, make appropriate choices, and expand their abilities by attempting challenging tasks (Perry, 1998;Perry & VandeKamp, 2000;Wharton-McDonald et al, 1997).…”
mentioning
confidence: 99%